Laparoskopsko pridobivanje potencialnih matičnih celic jajčnika pri bolnicah s prezgodnjo menopavzo - Vogler, Andrej (Endoskopska revija, 2012)
Background: Women with premature ovarian failure (POF) are unable to conceive and have a genetically related child with their own oocytes. The presence of stem cells in an adult human ovary has not yet been definitively established. The aim of our study was to collect laparoscopically putative stem cells from adult ovaries of women with POF, and to derive oocytes from stem cell cultures. Patients and Methods: Eight infertile women with POF were included in our study. In all patients laparoscopy was performed and the following techniques of putative stem cells collection were used: scratching and brushing the ovarian surface, ovarian biopsy and rinsing the ovarian surface. A part of the tissue was stained with cytokeratin to determine the presence ofovarian surface epithelium. The collected ovarian cells were cultured for 16days and cell differentiation was followed morphologically. Results: Thick ovarian surface epithelium was confirmed and ovarian cell cultures were successfully established in 7 of the 8 women. On the 5th day of culturing, oocyte-like cells with a germinal vesicle and zona pellucida were identified. In some of these cells a spindle was confirmed. Additionally, some blastocyst-like structures were found in all patients. Somatic cells, including neuron-like and myoblast-like cells and a layer of epithelial cells,were confirmed in the cell culture, too. Conclusions: Our work has empirically proved the presence of ovarian stem cells in patients with POF. These cells can be collected using a relatively straightforward laparoscopic procedure. The differentiation of oocyte-like and blastocyst-like cells in theovarian cell culture strongly supports the existence of ovarian stem cells in women with POF.
Keywords: Jajčnik, odpoved, prezgodnja; Ovarian Failure, Premature; Infertility, Female; Neplodnost ženska; Matične celice; Laparoscopy; Laparoskopija; Oocytes; Jajčne celice; Stem Cells; Adult; Odrasli; Oploditev in vitro; in vitro fertilization; Cells, Cultured; Fertilization In Vitro; Celične kulture; neplodnost; menopavza